Application of multimedia in teaching Hajj - Isa, Hafizuddin; Zeki, Akram M. (IIUM Press, 2015)
Information and communication technologies (ICT) have provided great changes in all aspects of life nowadays. The technology is developing day by day and ICT has been used widely across the world. In term of education, IT also changes the learning approach in some aspect. ICT infrastructure helps a lot in educational aspect especially in the higher institutions of learning. This chapter introduces another teaching approach using multimedia technology. This multimedia is about Hajj guideline pilgrims using 3D animation. This is another method of learning after using booklet, DVD etc.